1984
DOI: 10.1007/bf01410254
|View full text |Cite
|
Sign up to set email alerts
|

Influence of specimen thickness on isothermal crystallization kinetics. A theoretical analysis

Abstract: In the DSC technique, isothermal crystallization experiments are usually performed on thin flat specimens, but their interpretation generally uses theories developed for an unbounded volume. In this paper, isothermal crystallization of spherical entities in the volume limited by two parallel infinite planes is considered. Our model, derived from Avrami's theory, gives an analytical expression for the transformed volume fraction as a function of time. It is shown that the influence of thickness becomes importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 16 publications
4
61
0
Order By: Relevance
“…The observed differences may be due to truncation effects. In a recent paper [10], Escleine et al have shown that the truncation of spherulites by the specimen surfaces can induce a decrease of the Avrami exponent. This decrease, which can range from 0 (unbounded volume) to 1, is particularly important when the specimen thickness is of the order of or smaller than the final average spherulite radius.…”
Section: Nucleationmentioning
confidence: 98%
“…The observed differences may be due to truncation effects. In a recent paper [10], Escleine et al have shown that the truncation of spherulites by the specimen surfaces can induce a decrease of the Avrami exponent. This decrease, which can range from 0 (unbounded volume) to 1, is particularly important when the specimen thickness is of the order of or smaller than the final average spherulite radius.…”
Section: Nucleationmentioning
confidence: 98%
“…While these phenomena do take place in most cases, spherulite impingement and spatial confinement are also responsible for a significant part of the Avrami exponent deviation as they are inherent in all polymers and do not depend on polymer chain properties. A complex dependence of overall crystallization kinetics on crystallizing volume geometry as well as crystallization parameters, especially growth and nucleation rates had been shown by Escleine et al [13] Several previous studies have revealed the influence of spatial confinement and spherulite impingement on observed crystallization kinetics. Mathematical formulations taking into account the influence of spatial confinement on crystallization kinetics were first proposed by Escleine et al [13] and Billon et al [14] Further development included adding probabilistic functions in order to attempt to describe the random nature of homogeneous nucleation.…”
Section: Introductionmentioning
confidence: 93%
“…A complex dependence of overall crystallization kinetics on crystallizing volume geometry as well as crystallization parameters, especially growth and nucleation rates had been shown by Escleine et al [13] Several previous studies have revealed the influence of spatial confinement and spherulite impingement on observed crystallization kinetics. Mathematical formulations taking into account the influence of spatial confinement on crystallization kinetics were first proposed by Escleine et al [13] and Billon et al [14] Further development included adding probabilistic functions in order to attempt to describe the random nature of homogeneous nucleation. [15] These studies suggested a noticeable decrease in the Avrami exponent due to spatial confinement.…”
Section: Introductionmentioning
confidence: 93%
“…In addition, the growth velocity may be ascertained from fits of the model to data for prenucleated ''thin'' films whose phase change kinetics are expected to slow noticeably when the mean crystallite size is comparable to the film thickness. 13,14,[17][18][19] Finally, based upon these results and the transition kinetics of large, non-pre-nucleated specimens, the temperature dependence and rate of nucleation can be computed.…”
Section: ͑2͒mentioning
confidence: 99%
“…More typically, a large number of nucleation events occur during the course of phase change and hence the mean grain size is often far smaller than specimen dimensions. In this case, isothermal transformation kinetics can usually be described by the Kolmogorov-Johnson-Mehl-Avrami equation or its derivatives, [1][2][3][4][5][9][10][11][12][13][14][15][16] e.g.,…”
Section: Introductionmentioning
confidence: 99%